IMPLEMENTATION CLEAN AND HEALTHY LIVING BEHAVIOR AT ELEMENTARY SCHOOL LEVEL IN MEDAN CITY - Zahra, Nabila Isma; Tumangger, Suro Rahmadhona; Aulia, Dinda Zalfa; Siregar, Putra Apriadi; Siregar, Prima Yanti (Pusat Studi Gender dan Anak, 2024)
Clean and Healthy Living Behavior Program in schools push students, teachers, and society environment school For do pattern life Healthy For create healthy school. This program reach objective For give experience Study or create condition for individual, family, group and society with open track communication, giving information, and doing improving education knowledge , attitudes , and behavior. Many diseases are caused Because behavior life clean and healthy still not enough implemented in schools like Diarrhea , worms , filariasis, dengue fever and vomiting. Research result show that application Clean and Healthy Living Behavior at the elementary school level in the Medan City Health Center working area in October-December 2023 experienced fluctuations (fluctuating) or the value was not constant. Indicators that influence Clean and Healthy Living Behavior in schools Already appropriately improved Again For child conscious school will importance doing Clean and Healthy Living Behavior at school. Based on research use Time Series analysis using the Sequence Charts method can be concluded that elementary school level Clean and Healthy Living Behavior activities in the Medan City Health Center work area in October-December 2023 experienced fluctuations (up and down) or their values were not constant. Indicators that influence clean and healthy living behavior in schools Already appropriately improved Again For child conscious school will importance doing clean and healthy living behavior at school.